Pengaruh Kesenangan Konsumen, Materialisme, Dan Kesesuaian Diri Terhadap Cinta Merek Pada Konsumen Produk Skincare - Kristianti, Saskia; Putra, Harmanda Berima; Annisa, Intan Tri; Nurfatimah, Siti Nuke (Jurnal Orientasi Bisnis dan Entrepreneurship (JOBS), 2024)
There are still a lot of brands today that fail to survive in their respective industries. Brand development is hindered by the absence of a psychological strategy, such as fostering emotional connections. The purpose of this study is to determine how consumer pleasure, materialism, and self-conformity affect brand loyalty. Quantitative methods are used in the research approach. Purposive sampling is the sample technique that is applied. A Google Form was utilized to collect data from respondents, yielding 202 student responses. Multiple linear regression analysis is used in research analysis. According to the study's findings, materialism and customer satisfaction boost brand loyalty. In the meantime, brand loyalty is unaffected by self-conformity. Our study has a number of practical and conceptual ramifications.  From a conceptual standpoint, the study offers guidance for future investigations, such as broadening the causes and effects of brand love, including brand romance, brand loyalty, and satisfaction. Empirically speaking, study findings indicate that managers and businesses alike must be mindful of brand positioning tactics. When it comes to using skincare products, people put pleasure and materialistic aspects first.